Underware Rules Terintegrasi Akhlak Islam sebagai Pencegahan Child Abuse di Sekolah Dasar Negeri - Unsi, Baiq Tuhfatul; Nadiroh, Intan (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
In recent times, sex education has become an urgent matter to be conveyed, considering the many cases of sexual violence targeting children, especially in educational institutions. This community service was conducted at two State Elementary Schools in Tanjunganom Nganjuk. The CBR method has four stages: laying the foundation, planning, information gathering and analysis and acting on findings. This community service shows the results that sex education at Tanjunganom Elementary School is carried out through three strategic steps; the first is collaboration, which is carried out together with KKG PAI Tanjunganom. Second is material construction, namely determining the material adopted through underware rules, which is then integrated with Islamic education. Third, stimulus provision, namely in the form of a competition with the theme My Body is My Own and Good Secret and Bad Secret. In the implementation of sex education, it can significantly increase students' knowledge. The implementation of sex education cannot be separated from the provision of material about Islamic morals. In addition, sex education at the Elementary School level, which is carried out through various methods, must also be balanced with discussions and lectures as an actualization of the construction of material in children's memories. This form of education is an effective preventive step in reducing the number of cases of sexual violence.